Determinants of climate change: is financial development a significant contributor to climate change - Lim, Angie; Lim, Guo Wei; Loh, Kah Chye; Loo, Pui Kuan; Wong, Kang Xian (2020)
The main purpose of this study is to study the determinants of climate change in 5 of the ASEAN countries from the period of 1996 to 2015. It also studies about the significance of Financial Development in the issue of climate change and how it interacts with other determinants and further causes climate change. The data used in this research is secondary data with a total number of observations of 100. In this research, some variables have been found to be significant in affecting climate change and some variables have been found to interact with financial development and further affects climate change. The emission of carbon dioxide would increase when foreign direct investment and economic growth interacts with financial development. This shows that with higher financial development, foreign direct investment and economic growth would further cause climate change in the 5 ASEAN countries. However, when renewable energy interacts with financial development, it would decrease the emission of carbon dioxide. This means that when the country is developed, it would have enough resources to develop renewable energy and reduce climate change effectively. As a conclusion, financial development does play a significant role in the issue of climate change in the 5 ASEAN countries.